2020
DOI: 10.5114/ada.2020.96909
|View full text |Cite
|
Sign up to set email alerts
|

Can allergy patch tests with food additives help to diagnose the cause in childhood chronic spontaneous urticaria?

Abstract: Introduction Chronic spontaneous urticaria (CSU) is characterized by the onset of symptoms which are not induced by specific triggers, but are rather spontaneous. A considerable number of patients report that foods or food additives might be responsible for their chronic urticaria. Aim To determine the prevalence of sensitization to food additives in children with CSU using atopy patch tests (ATP). Material and methods Atopy patch tests for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In all the patients with positive OC, carmine patch tests were definitely negative, so we did not find any contact allergy coexistence. Other authors showed positive carmine patch tests in children, however no oral challenge was performed [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all the patients with positive OC, carmine patch tests were definitely negative, so we did not find any contact allergy coexistence. Other authors showed positive carmine patch tests in children, however no oral challenge was performed [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the PT technique with common aero- and food- allergens instead of the standard contact allergens, has also been reported. 17 This process, known as the atopy PT, demonstrated that 17 of 120 children with CSU (14.1%) were sensitized to food additives. The authors concluded that the atopy PT may be useful in CSU.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been postulated that house dust mite allergens penetrate the stratum corneum and activate Langerhans and mast cells. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food additives are natural or synthetic agents such as dyes, preservatives, and artificial sweeteners, which can act as potent pseudoallergens (Table 5). 44 A recent study has highlighted Azorubine and Cochineal red to be the food additives with the highest sensitivity 45 . Most food additives are excluded as part of PAF diets.…”
Section: Elimination Dietsmentioning
confidence: 99%